1997
DOI: 10.1111/j.1600-0773.1997.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time Interval between Food and Drug Ingestion on the Absorption of Oxybutynin from a Controlled‐Release Tablet

Abstract: Abstracl:The effect of time interval between food and drug ingestion on the bioavailability of oxybutynin was investigated in a randomized, three-phase cross-over study in 3 1 healthy volunteers. The serum concentrations of oxybutynin and the metabolite, N-desethyloxybutynin were measured up to 48 hr after ingestion of a controlled-release 10 mg oxybutynin tablet either in fasting state, 2 hr after breakfast or I hr before. The C , , , of both oxybutynin (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Lukkari et al [19] investigated the effect of food on the prevalence of drug related adverse effects. The authors confirmed that a meal resulted in a significant increase in C max both for the drug and its metabolite, and increased AUC for N-deethyloxybutynin.…”
Section: Resultsmentioning
confidence: 99%
“…Lukkari et al [19] investigated the effect of food on the prevalence of drug related adverse effects. The authors confirmed that a meal resulted in a significant increase in C max both for the drug and its metabolite, and increased AUC for N-deethyloxybutynin.…”
Section: Resultsmentioning
confidence: 99%
“…To alleviate these effects by maintaining a more constant level of oxybutynin, an ER formulation is commonly used [11]. Studies have shown that although there are alterations in oxybutynin ER pharmacokinetics when it is taken in a fasting state versus a fed state, the differences are not clinically signifi cant and should not affect the therapeutic response [4,12,13]. However, it also has been shown that the presence of food may increase the initial release of oxybutynin from its ER formulation, producing a slightly higher concentration peak and the possibility for increased nonbladder effects such as dry mouth.…”
Section: Effects Of Food On the Treatment For Oabmentioning
confidence: 99%
“…However, it also has been shown that the presence of food may increase the initial release of oxybutynin from its ER formulation, producing a slightly higher concentration peak and the possibility for increased nonbladder effects such as dry mouth. Therefore, it may be recommended to take oxybutynin ER 1 hour before meals to maintain more consistent and level oxybutynin concentrations, especially in individuals prone to systemic side effects [4,12].…”
Section: Effects Of Food On the Treatment For Oabmentioning
confidence: 99%
“…OXB and/or its formulation(s) are official in USP, EP and BP. Being the drug of first choice in treating UI, OXB has been studied extensively for its pharmacodynamic properties [5,6] and pharmacokinetic parameters [7][8][9].…”
Section: Introductionmentioning
confidence: 99%